Communicating the Risk of Violent and Offending Behavior: Review and Introduction to this Special Issue. (February 2015) - Hilton, N. Zoe; Scurich, Nicholas; Helmus, Leslie‐Maaike
<x xml:space="preserve">Abstract</x> How to communicate risk of recidivism in correctional and forensic contexts has been a subject of scholarly discussion for two decades. This emerging literature, however, is sparse compared with studies on the assessment of risk for violent and offending behavior. In this special issue of Behavioral Sciences and the Law, we have gathered together empirical and review papers exemplifying promising directions and methodologies. We begin with a review of the state of the field, and lessons that can be drawn from research into medical risk assessment and risk communication, finding that many of the same principles apply to the forensic context. How risks are framed, and how numerate assessors are, affects how risk information is understood and applied. We discuss the existing research bearing on these issues, as well as the conceptual, practical, empirical, and legal implications of communicating risk using numerical or categorical risk terms. Along with the seven articles in this volume, we suggest directions for future research on measuring and communicating change, understanding and managing the statistical literacy of those who use and communicate risk assessments, and developing a theoretical framework for forensic risk communication research. We hope this volume will help integrate and invigorate research into forensic risk communication. Copyright © 2015 John Wiley & Sons, Ltd.